(untitled) (Anuário Antropológico, 2023)
Based on research data obtained from two different contexts of social vulnerability in Brazil, this paper will analyze consumption strategies and how they are perceived. The leading figures of these stories are female peasants, beneficiaries of the Bolsa Família Program and women living in urban areas who had their income reduced because of the COVID-19 pandemic and had therefore to join the Boleto+1 Facebook group. Among female farmers, the ethnographic research was conducted between 2016 and 2018, while the research with Boleto+1 members was carried out in 2020, in the first months of the pandemic, via digital platforms.